Socioeconomic Impacts of Land Acquisition for the Yogyakarta Toll Road: Using Inferential Statistics - Nurpita, Anisa; Kumorotomo, Wahyudi; Susanto, Nurhadi (JAMPE (Journal of Asset Management and Public Economy), 2025)
Rapid infrastructure development in the transportation sector has significant implications for land acquisition, including residential and agricultural land. The conversion of agricultural land poses challenges by reducing green open spaces and disrupting the socioeconomic conditions of affected communities, particularly farming households. This study examines the socioeconomic consequences of land acquisition in the Yogyakarta toll road construction, focusing on changes in employment, agricultural productivity, and asset ownership. Data were collected through a structured questionnaire survey targeting affected households, selected using purposive sampling. The analysis employs descriptive statistics to identify patterns and trends. This study also performs correlation tests to examine relationships between variables and communities' willingness to release land. The findings indicate that 22% of respondents lost their jobs due to land acquisition, and 26% have not yet secured alternative employment, highlighting economic adaptation challenges. Additionally, 44% of respondents reported that their acquired land was agricultural. It leads to a decrease in productivity and income for farmers. Land conversion has also altered asset ownership, particularly for farmers whose livelihoods depended on their land. The study contributes empirical evidence on the socioeconomic impacts of large-scale infrastructure projects, emphasizing employment challenges, land use changes, and financial stability. The correlation analysis reveals a weak but statistically significant relationship between improved road access and residents' willingness to relinquish land. These findings provide valuable insights for policymakers, infrastructure planners, and stakeholders to develop mitigation strategies, including job creation programs, financial support for displaced farmers, and policies ensuring sustainable land management and community engagement in future land acquisition processes.